Strength of Plantar- and Dorsiflexors Mediates Step Regularity During a High Cognitive Load Situation in a Cross-sectional Cohort of Older and Younger Adults. Issue 4 (October 2020) - FallahTafti, Farahnaz; Watson, Kristen; Boron, Julie Blaskewicz; Myers, Sara A.; Schmid, Kendra K.; Yentes, Jennifer M.
Abstract : Background and Purpose: Completing simultaneous tasks while standing or walking (ie, a high cognitive load situation [HCLS]) is inevitable in daily activities and can lead to interference in task performances. Age-related physical and cognitive changes may confound performance variability during HCLS in older and younger adults. Identification of these confounding effects may reveal therapy targets to maintain optimal physical function later in life. The aim of this study was to investigate the effect of increasing the difficulty levels of an additional motor task and restricting visual information, on gait parameters in younger and older adults while considering the effect of cognitive and physical covariates. Methods: Fifteen healthy younger and 14 healthy older adults were asked to complete assessments of cognitive function, balance, and strength. They were then asked to walk on a self-paced treadmill with or without carrying a plastic tray. Opaqueness of the tray (vision) and the presence of water in glasses placed on the tray (increasing task difficulty) were varied. Mean, standard deviation, and regularity (sample entropy) of step width and length were compared across conditions and groups using repeated-measures analyses of variance with and without covariate analysis. Only significantly correlated covariates of cognition, balance, and strength were entered into each model. Results and Discussion: Older adults had greater step width irregularity compared with younger adults across all conditions when controlling for concentric plantar- and dorsiflexion strength. A decline in strength may likely alter neuromuscular control of gait, specifically control of step width, which has been associated with fall risk in older adults. Adjusting for the same covariates revealed increased regularity of step length, as visual feedback from the feet was restricted. Specifically, step length was more regular while carrying an opaque tray compared with not carrying a tray. Visual restriction was a contributing factor, which led to more predictable gait kinematics, indicating the role of sensory information to enhance the adaptability during walking under HCLS. Conclusion: The knowledge of the regularity behavior of human movement can expand physical therapists' treatment approaches to promote further interactivity and coordination across body systems that model behavior of healthy young individuals. Targeting strength during therapy may provide additional benefits for gait performance under HCLS. Abstract : Supplemental Digital Content is Available in the Text.